Service Supply Chain Management in Malaysia: Feasibility towards Sustainable System - Choong Kei Shing; Gunalan SO Nadarajah; Santhirasegaran Nadarajan (International Journal of Supply Chain Management, 2014)
Service industry posts many improvement opportunities in supply chain system, adopting from the experiences in manufacturing industry. Though some global and local giant corporation has begun implementing a more systematic and complex supply chain system in the firm, the sustainability of the implementation is still in a challenging stage. This is highly due to the infant characteristic that the system bears in the new industries. Cost and quality constraints demands for service supply chain management in Malaysia's service firms to mature quickly in today's highly paced technological world. This includes on time delivery, raw material inventory control, planning, and quality control in service. The market focus migrates to post-industrialization leading a positive surge in service sector's growth. Keywords: supply chain management, sustainability, service industry